New place, new person?: is acclimatisation to university accompanied by change in scores on personality tests? - Nair, Vikas (2013)
Introduction: Personality Trait theories uncritically accept the lay perspective of personality as an internal phenomenon linked to individuality and agency. This view flies in the face of empirical evidence demonstrating environmental influences on behaviour (Bargh & Ferguson, 2000). The idea that agency resides within individuals, and that a separation exists between individuals and their environment, has long been contested by theorists and clinicians arguing for acknowledgement of contextual factors (Skinner, 1971; Smail, 1999).